Anatomic pathology board review - Lefkowitch, Jay H. (Saunders Elsevier, 2006)
Containing colour images of microscopic and gross specimens, this text serves as a comprehensive review for the Anatomic Pathology board certification examination and in-service training exams. It contains chapters covering general pathology, the major organ systems and other topics, including immunohistochemistry, cytopathology, and more.